KETERBATASAN BADAN PENYELESAIAN SENGKETA KONSUMEN DALAM PENYELESAIAN SENGKETA KONSUMEN - Tami Rusli (Masalah-Masalah Hukum, 2014)
Default Paragraph Font;hps;Consumer Dispute Settlement Board which is expected to be able to provide a fair settlement to the disputed parties turns out in practice causing confusion for those involved in the implementation process especially when there is an inclusion of the judiciary role in investigating the case of BPSK rejection decision. The problem is how the limited ability of UUPK law in the consumer disputes resolution is. The law (legislation) in relation to consumer protection has limited capabilities so it cannot realize the purpose of the law. The setting of BPSK there are limitations associated with the setting position of the judiciary.